The College Students’ Satisfaction for Using Edmodo - the Learning Technology Application as E-Learning Media and Learning Effectiveness Improvement in Economic Higher Institution Mahardika Surabaya (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This is quantitative research. The purpose of this study was to reveal the use of Edmodo free learning applications on student satisfaction and learning effectiveness.  The population of this study was students of the Mahardika Surabaya Economics College who took e-learning courses. While the sample is 160 students. Sampling was done by Non-Probability Sampling, namely by Accidental Sampling. The instrument used is in the form of a questionnaire. The data analysis used is path analysis. The results of the analysis prove that satisfaction has a significant effect on the effectiveness of learning. Student satisfaction affects the effectiveness of learning because they are satisfied with learning, service, and teaching. They can increase effectiveness, such as doing assigned assignments, presenting, studying, and discussing with colleagues or lecturers.